ANALISIS PENDAPATAN USAHATANI PADA KOPI TRADISIONAL DAN KOPI SAMBUNG DI DESA LUBUK KEMBANG, KEC. CURUP UTARA, KAB. REJANG LEBONG - Suhendra, Dori; Nurung, Muhammad; Reswita, Reswita (Jurnal AGRISEP, 2012)
This research was conducted in the Desa Lubuk kembang, Kec. Curup Utara, Kab. Rejang Lebong, Prov. Bengkulu. The purpose of this study are: 1) to calculate revenue on the traditional coffee farming and grafting coffee farming and 2) to determine the condition of efficiency in traditional coffee farming and grafting coffee farming and their difference. The amount of 68 farmers of coffee were chosen by using the accidental sampling method. The respondents of farmers’ group consist of 34 farmers. Data analysis used descriptive analysis. The results of this research showed that the average income of traditional coffee farming is Rp. 7,369,461,00/hectar/year, while the average farm income of grafting coffee farming of Rp. 18,792,149/hectar/ year. The average value of R/C ratio in traditional coffee farming was 3.37, while in grafting coffee farming was 3.85. These indicataed that coffe farming, both on traditional coffee farming and grafting coffee farming, were eficient.